Dynamics of cyanobacteria planktothrix species (Oscillatoriales: Phormidiaceae) in Earthen fish ponds, Northwestern Bangladesh - Yeamin Hossain .Md,; Abu Sayed Jewel .Md,; Bernerd Fulanda,; Ferdous Ahamed,; Sharmeen Rahman,; Saleha Jasmine,; Jun Ohtomi, (Universiti Kebangsaan Malaysia, 2012)
The seasonal abundance, dynamics and composition of the filamentous Cyanobacteria Planktothrix spp. was studied over a 1-year period in two storm-water-fed earthen fishponds in Rajshahi city, northwestern Bangladesh. Sampling was conducted monthly using plankton net (25 μm mesh size) and the samples preserved in 5% formalin. Water quality parameters including water temperature, transparency, pH, dissolved oxygen (DO), biological oxygen demand (BOD), free carbon dioxide (CO2), nitrite-nitrogen (NO2-N), nitrate-nitrogen (NO3-N), ammonium (NH4 +), oxidation reduction index (rH2) were recorded during each sampling. Two species; Planktothrix agardhii and Planktothrix rubescens were identified during the study with P. agardhii recording higher abundance (p<0.05) all year round. The Planktothrix cell density was highest during March: 3.06×106 cells/L and 1.23×106 cells/L in Pond-1 and 2, respectively. The abundance of P. agardhii was relatively higher in spring. The cell densities increased with increasing temperature, pH, and nutrient concentration. Lower cell densities were recorded during periods of high BOD. The results of this study provide a useful guide for aquaculturists and other environmental scientists for the management of the cyanotoxin producing algal blooms of Planktothrix spp. in fertilized fish ponds and other aquatic habitats.